Net plant interactions are highly variable and weakly dependent on climate at the global scale - Yang, Xuejun; Gómez‐Aparicio, Lorena; Lortie, Christopher J.; Verdú, Miguel; Cavieres, Lohengrin A.; Huang, Zhenying; Gao, Ruiru; Liu, Rong; Zhao, Yonglan; Cornelissen, Johannes H. C.; Chase, Jonathan (Ecology letters, 2022)
Although plant–plant interactions (i.e. competition and facilitation) have long been recognised as key drivers of plant community composition and dynamics, their global patterns and relationships with climate have remained unclear. Here, we assembled a global database of 10,502 pairs of empirical data from the literature to address the patterns of and climatic effects on the net outcome of plant interactions in natural communities. We found that plant interactions varied among plant performance indicators, interaction types and biomes, yet competition occurred more frequently than facilitation in plant communities worldwide. Unexpectedly, plant interactions showed weak latitudinal pattern and were weakly related to climate. Our study provides a global comprehensive overview of plant interactions, highlighting competition as a fundamental mechanism structuring plant communities worldwide. We suggest that further investigations should focus more on local factors (e.g. microclimate, soil and disturbance) than on macroclimate to identify key environmental determinants of interactions in plant communities. In this work, we quantify global patterns of plant–plant interactions by synthesising a global data set comprising 10,502 pairs of empirical comparisons of plant performances with versus without neighbours across all seven (sub‐)continents and over a century of research. Based on our global database, we are able to show for the first time that competition occurs more frequently in the net outcome of plant–plant interactions in plant communities worldwide. Our results confirm the traditional wisdom that competition is a key mechanism structuring natural communities and are crucial to understand the key role of plant–plant interactions in determining community compositions at the global scale.